2018
DOI: 10.1007/s00193-018-0858-5
|View full text |Cite
|
Sign up to set email alerts
|

Blast wave propagation in survival shelters: experimental analysis and numerical modelling

Abstract: The propagation of blast and shock waves in confined environments is a complex phenomenon; yet, being able to derive valid predictions of such phenomena is highly relevant, for example, when it comes to the assessment of protection of personnel in military environments. This study looks at the propagation of blast waves inside a compound survival shelter. Experimental analyses are performed on a small-scale model of the actual configuration of the shelter subjected to the detonation of an explosive charge at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The work is divided in two main parts: the influence of different parameters concerning experimental pressure signals measured by Cac ¸oilo et al [19] in a confined environment such as survival shelters, and the possibility to simplify those signals according to their total impulse.…”
Section: Parametric Analysis On the Behaviour Of A Corrugated Platementioning
confidence: 99%
“…The work is divided in two main parts: the influence of different parameters concerning experimental pressure signals measured by Cac ¸oilo et al [19] in a confined environment such as survival shelters, and the possibility to simplify those signals according to their total impulse.…”
Section: Parametric Analysis On the Behaviour Of A Corrugated Platementioning
confidence: 99%
“…Generally, the accuracy of these methods is controlled by the coarseness of the element mesh forming the environment or the step size used in the calculation process. This is discussed further by Caçoilo et al (2018), who studied the propagation of blast waves inside a survival blast chamber using an LS-DYNA numerical model. Through comparing the numerical results to a physical experiment, the authors reported specific impulse errors below 19% when using a mesh size of 3.25 mm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other simplified approaches exist [16,17], but to evaluate possible shadowing or amplification effects for which no test data are available, robust numerical models are crucial [18]. Naturally, numerical solutions are dependent on the discretisation [19]-finer discretisation gives, in general, more accurate solutions but adds to the computational time.…”
Section: Introductionmentioning
confidence: 99%